Functions of protein phosphatase-6 in NF-κB signaling and in lymphocytes. (15th June 2017) - Ziembik, Magdalena A.; Bender, Timothy P.; Larner, James M.; Brautigan, David L.
Abstract : Protein phosphatase-6 (PP6) is a member of the PPP family of Ser/Thr phosphatases involved in intracellular signaling. PP6 is conserved among all eukaryotes, and genetics in model organisms indicates it has non-redundant functions relative to other PPP phosphatases. PP6 functions in association with conserved SAPS subunits and, in vertebrate species, forms heterotrimers with Ankrd subunits. Multiple studies have demonstrated how PP6 exerts negative control at different steps of nuclear factor kappaB signaling. Expression of PP6 catalytic subunit and the PPP6R1 subunit is especially high in hematopoietic cells and lymphoid tissues. Recent efforts at conditionally knocking out genes for PP6c or PP6R1 (SAPS1) have revealed distinctive effects on development of and signaling in lymphocytes.